Effects of Specific Electric Field Stimulation on the Release and Activity of Secreted Acid Phosphatases from Leishmania tarentolae and Implications for Therapy - Benjamin M. Dorsey; Cynthia L. Cass; David L. Cedeño; Ricardo Vallejo; Marjorie A. Jones (Pathogens, 2018)
Leishmaniasis is a neglected tropical disease with 1.6 million new cases reported each year. However, there are few safe, effective, and affordable treatments provided to those affected by this disease. Still under-appreciated as potential pharmaceutical targets, especially for cutaneous leishmaniasis infections, are the two isozymes of secreted acid phosphatase (SAP). These enzymes are involved in the survival of the parasite in the sand fly vector, and in infecting host macrophages. While the application of electric or electromagnetic fields as a medicinal therapeutic is not new, the utility of electric field application for the treatment of leishmaniasis is under studied. Studies involving the effects of electric fields on the cell secretion of SAP or the activity of SAP that has been secreted prior to electrical stimulation have not yet been reported. This work is the first report on the effect of specific electric fields on the activity of Leishmania tarentolae secreted acid phosphatases and the modulation of this secretion from the cells. In addition, the kinetic constants for the enzyme isoforms were determined as a function of days in culture and removal of carbohydrate from the glycosylated enzymes, while using a glycosidase, was shown to affect these kinetic constants.